The corporate debt market: A firm-level panel study for India - Basudeb Guha-Khasnobis; Saibal Kar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Traditionally, firms in India have shown a low preference towards debt financing, despite its advantages. Using panel data from 450 firms during 1992-93 and 2003-04, we attempt to identify factors which could explain the pattern of financing of manufacturing firms in India and the key determinants of their debt structure. We examine the roles of age of the firm, long term borrowing and net sales in affecting its debt structure.
Keywords: C51; G11; G31; G32; 330; corporate debt; leverage; manufacturing firms; panel data; India; Fremdkapital; Kapitalstruktur; Verarbeitendes Gewerbe; Indien